Peran Mediasi Good University Governance Terhadap Kinerja Utama Perguruan Tinggi - Akidah Fitrah; Mustiningsih Mustiningsih; Etatok Rindang Karjo; Arif Prastiawan (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: This research aims to empirically test the influence of performance-based budgeting and remuneration on the main performance of higher education institutions which is mediated by good university governance Methodology/approach: This research is causal research with a quantitative approach using path analysis. The data used is primary data obtained from a sample of 42 people by distributing questionnaires using Google Form. Answer measurement uses a Likert scale. Findings: Performance-based budgeting mediated by good university governance has a significant effect on the main performance of higher education institutions. Remuneration mediated by good university governance has a significant effect on the main performance of higher education. Performance-based budgeting has a significant effect on good university governance. Remuneration has a significant effect on good university governance. Performance-based budgeting cannot directly improve the main performance of higher education institutions because it does not have a significant effect. Direct remuneration cannot improve the main performance of higher education because it does not have a significant effect. Good university governance has a significant effect on the main performance of higher education. Practical implications: Improving higher education performance can be done through the application of good university governance principles such as transparency, accountability, responsibility, independence and justice as well as the implementation of performance-based budgets and effective remuneration to realize the implementation of good university governance. Originality/value: There are many research results on performance-based budgeting and remuneration on higher education performance with inconsistent results, so the research was conducted to fill the research gap in previous research by using good university governance as a mediating variable to improve higher education performance from the implementation of performance-based budgeting and remuneration.